A highly efficient nano-graphite-doped TiO2 photocatalyst with a unique sea-island structure for visible-light degradation. Issue 4 (24th January 2020) - Yang, Huiyu; Zhai, Lisha; Li, Ke; Liu, Xin; Deng, Bo; Xu, Weilin
Abstract : A nano-graphite-doped TiO2 composite, C-TiO2, was fabricated by atomic layer deposition (ALD) of TiO2 onto carbon fiber fabrics (CFFs), followed by calcination. Abstract : A nano-graphite-doped TiO2 composite, C-TiO2, was fabricated by atomic layer deposition (ALD) of TiO2 onto carbon fiber fabrics (CFFs), followed by calcination. The morphology and structure of the C-TiO2 composite were characterized by various techniques. The photocatalytic activity of C-TiO2 was compared with that of commercial P25. Results revealed that the nano-graphite/TiO2 "islands" with diameters of ∼5.5 nm were uniformly embedded inside the graphite "sea". Nano-graphite sheets closely contacted with TiO2, which formed Ti–O–C bonds between nano-graphite and TiO2 . The as-prepared C-TiO2 showed 2.1-fold higher photocatalytic activity than that of P25 and the reported C-TiO2 composite under visible light. C-TiO2 could effectively degrade MB at a removal rate of up to 93.1% even after 6 cycles of repeated usage.